1994
DOI: 10.1007/bf00182351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the route of administration on the biodistribution of radioiodinated OV-TL 3 F(ab′)2 in experimental ovarian cancer

Abstract: The effect of the route administration on the distribution of radioiodinated OV-TL 3 F(ab')2 was studied in Balb/c female mice with intraperitoneal or subcutaneous ovarian carcinoma xenografts. In the intraperitoneal tumour model in which both ascites and solid tumour deposits were present, intraperitoneal administration resulted in a lower estimated radiation dose to blood as compared with intravenous administration. In this model normalization to equal estimated radiation doses to blood for both routes of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…in humans) did not affect the magnitude of the response to endotoxin. This lack of difference in the response to the route of administration is supported by other work, including fever production after endotoxin administration (3), antibody treatment in a tumor model (33), and clondronate administration and deposition in bone (20). The physiological response (i.e., blood pressure, heart rate, and temperature) in humans in our present work is comparable to those of previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…in humans) did not affect the magnitude of the response to endotoxin. This lack of difference in the response to the route of administration is supported by other work, including fever production after endotoxin administration (3), antibody treatment in a tumor model (33), and clondronate administration and deposition in bone (20). The physiological response (i.e., blood pressure, heart rate, and temperature) in humans in our present work is comparable to those of previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Another group demonstrated that HLA I F(ab’) 2 caused rapid neutrophil recruitment and acute rejection of human skin grafts on immunodeficient mice (18). We attempted confirm our findings in vivo with an MHC I F(ab’) 2 fragment, but were unable to achieve consistently detectable levels of circulating antibody, likely due to their short half-life in vivo (82). Nevertheless, the data reported here show that P-selectin is a critical initiator which facilitates capture of monocytes from the circulation by graft endothelium in a long-term vascularized model of AMR.…”
Section: Discussionmentioning
confidence: 92%
“…only has limited effect on the targeting of i.p. growing tumors 19, 20, 21, 22, 23. Colcher et al investigated the efficacy of intracavitary radiolabeled MAb administration and demonstrated the advantage of the concomitant use of intracavitary and i.v.…”
Section: Discussionmentioning
confidence: 99%